Analisis Pengaruh Media Pendinginan pada Proses Perlakuan Panas Baja Hadfield terhadap Struktur Mikro dan Kekerasan - Wahyudi, Haris; Haryanto, Rofi Nur (Fakultas Teknik, Universitas Lampung, 2024)
Hadfield steel is steel with a content of 10-14% Mn and 1.0-1.4% C. Casting Hadfield steel contains carbide (Fe, Mn)3C at grain boundaries which can reduce strength so that it is given heat treatment so that the carbide dissolves. Rapid cooling of Hadfield steel in aqueous media prevents the formation of carbides at the grain boundaries. However, the cooling medium affects the cooling rate which changes the microstructure and mechanical properties of Hadfield steel. The purpose of this study was to analyze the effect of the cooling media water, ice water and oil in the heat treatment process on the microstructure and hardness of Hadfield steel. The heat treatment was initiated using a pre-austenizing temperature of 700℃ with a holding time of 60 minutes, followed by austenizing temperatures of 1150℃ and 1200℃ with a holding time of 30 minutes. After that, rapid cooling using the media of water, ice water and oil is then carried out mounting, grinding, polishing and etching. Testing the microstructure using an optical microscope and SEM while the Vickers hardness test. The results showed that heat treatment at 1150℃ followed by water+ice cooling produced a higher amount of carbide compared to water and oil, whereas at 1200℃ heat treatment with water+ice cooling produced a lower amount of carbide compared to water and oil. The highest hardness value was 185.1 HV at 1150℃ heat treatment followed by water+ice cooling, while the lowest hardness value was 174.3 HV produced by 1150℃ heat treatment with oil cooling. The highest hardness value of 187.6 HV was produced by heat treatment at 1200℃ followed by water cooling, while water+ice cooling produced the lowest hardness value of 168.2 HV.